Unprecedented Insight into Diffusion by Monitoring the Concentration of Guest Molecules in Nanoporous Host Materials - Kärger, Jörg; Kortunov, Pavel; Vasenkov, Sergey; Heinke, Lars; Shah, Dhananjai B.; Rakoczy, Rainer A.; Traa, Yvonne; Weitkamp, Jens (Angewandte Chemie International Edition, 2006)
How many guests? Interference microscopy is used to monitor the concentration of guest molecules in a ferrierite zeolite. The micropore diffusivities are determined as a function of loading through the microscopic application of Fick's second law. This method can be used to study isotropic and anisotropic diffusion, as well as to locate and quantify surface barriers and internal defects.